Induction of Somatic Embryogenesis in Sengon (Falcataria moluccana) With Thidiazuron and Light Treatments - . Dorly; Ence Darmo Jaya Supena; Ari Sunandar (Bogor Agricultural University, Indonesia, 2017)
Falcataria moluccana is important for reforestation and afforestation in Indonesia. However, epidemic of gall rust disease in F. moluccana plantations decreases its productivity. Genetic engineering is an alternative solution to against gall rust disease. Somatic embryogenesis is an efficient in vitro plant regeneration for successful plant improvement through genetic engineering. The objective of this study was to investigate the effect of thidiazuron and light treatments on the induction of somatic embryogenesis of F. moluccana. The effects of thidiazuron concentration (5, 10 or 15 μM) and light (continuous light, 7 days of dark followed by light, or continuous dark) on the induction of somatic embryogenesis in leaf explants were assessed. The highest production of somatic embryos was obtained in 5 μM thidiazuron and dark treatments for 7 days followed by light in Murashige and Skoog medium supplemented with 1.2 g/L proline. Histological analysis in globular and cotyledon stages confirmed that cells had progressed to secondary somatic embryogenesis. This research needs more improvements to become a successful and efficient somatic embryogenesis method and as a potential method for successful plant improvement through genetic engineering in F. moluccana.